2017
DOI: 10.1039/c7ra00146k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the elastic–plastic transition of a cylindrical coating/substrate composite under normal compression

Abstract: Numerical investigation on the plastic initiation of a coated cylinder in contact with a rigid plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Combining eqs , , and , the maximum contact pressure stress of the CrN coatings is decreased and the position of the maximum stress is simultaneously moved into the coating interface as the coating thickness increases, both of which have been identified by many researchers using the FEM simulation. ,, Also, according to the von Mises yield criterion , and combining eqs , , and , the stress (σ eq ) at any location on the depth directions ( z axis) can be expressed as follows It has been reported that ϑ for the CrN coating is 0.25. Hence, the maximum depth of contact stress is 19.35 μm under the load of 10 N, which is bigger than the thickness of CrN­(5 h) coatings, but much smaller than the thickness of CrN­(12 h) coatings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining eqs , , and , the maximum contact pressure stress of the CrN coatings is decreased and the position of the maximum stress is simultaneously moved into the coating interface as the coating thickness increases, both of which have been identified by many researchers using the FEM simulation. ,, Also, according to the von Mises yield criterion , and combining eqs , , and , the stress (σ eq ) at any location on the depth directions ( z axis) can be expressed as follows It has been reported that ϑ for the CrN coating is 0.25. Hence, the maximum depth of contact stress is 19.35 μm under the load of 10 N, which is bigger than the thickness of CrN­(5 h) coatings, but much smaller than the thickness of CrN­(12 h) coatings.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Hertz solution, the contact pressure of the compressed coatings is distributed in a planes-strain model (Figure ). The parameter F represents the normal load and R represents the counterpart ball radius.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a cylindrical contact of a coating/substrate composite under normal compression, Mu et al [ 26 ] derived a critical force for an elastic‐plastic transition of the compressed coating: FC=normalπ·RD·σY2·true(1νC2true)·Cv2EnormalC, ${F}_{{\rm{C}}}=\frac{{\rm{\pi }}\cdot {R}_{{\rm{D}}}\cdot {<mpadded xmlns="http://www.w3.org/1998/Math/MathML">\sigma </mpadded>}_{{\rm{Y}}}^{2}\cdot (1-{<mpadded xmlns="http://www.w3.org/1998/Math/MathML">\nu </mpadded>}_{{\rm{C}}}^{2})\cdot {<mpadded xmlns="http://www.w3.org/1998/Math/MathML">C</mpadded>}_{{\rm{v}}}^{2}}{{E}_{{\rm{C}}}},$with Cv=1.164+2.977·νC2.914·0.25emνC2true(for νC=0.20.25emto0.25em0.5true). ${C}_{{\rm{v}}}=1.164+2.977\cdot {\nu }_{{\rm{C}}}-2.914\,\cdot \,{<mpadded xmlns="http://www.w3.org/1998/Math/MathML">\nu </mpadded>}_{{\rm{C}}}^{2}(\text{for}\ {\nu }_{{\rm{C}}}=0.2\,\text{to}\,0.5).$…”
Section: Resultsmentioning
confidence: 99%